1999
DOI: 10.1109/22.808983
|View full text |Cite
|
Sign up to set email alerts
|

Large- and small-signal IMD behavior of microwave power amplifiers

Abstract: Abstract-In this paper, large-signal intermodulation distortion (IMD) sweet spots in microwave power amplifiers are studied and predicted using a new mathematical basis. The variations in the IMD versus drive pattern with active bias point and the terminating matching networks are investigated. This nonlinear distortion model enabled the design of power amplifiers specially tailored to present a desired IMD versus drive-level pattern. For practical validation purposes, a MESFET case study and an illustrative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(94 citation statements)
references
References 7 publications
6
88
0
Order By: Relevance
“…IMD behavior in MESFET amplifiers has been treated in [3]. The analysis combines Volterra series for low input power with describing functions and harmonic balance for higher input power.…”
mentioning
confidence: 99%
“…IMD behavior in MESFET amplifiers has been treated in [3]. The analysis combines Volterra series for low input power with describing functions and harmonic balance for higher input power.…”
mentioning
confidence: 99%
“… Present model using matlab curve fittingtoolbox. Comparing these curves it is found that the error between the two curves is less than 2%, thus equation (6) is approximately the same as equation (4).…”
Section: Theoretical Analysismentioning
confidence: 66%
“…The traditionally nonlinear analysis method is more difficult because it uses more complicated mathematical solutions, such as voltera series [3] based on small signal model transistors, while it hardly describes the large signal nonlinearity [4] for the omission of the DC offset with AC input. Wu Tuo Chen, Hongyi and Qian Dahong [5] introduced a model to improve the linearity of RF PAs; this model indicates that the DC bias resistance can affect the nonlinearity, but this model is very difficult to study, and more complicated to make any modification required for improvement of linearity and efficiency, this paper introduces a computer simulation analytic model to improve the linearity and efficiency of RF linear PAs.…”
Section: Introductionmentioning
confidence: 99%
“…Carvalho and Pedro have mathematically formulated the overall IMD behaviour by integrating the small and large signal contributions in closed form analytical expression [21].…”
Section: A Dynamic Gate Bias Techniquementioning
confidence: 99%
“…There are some particular PA features that provide a way to escape from this apparent dead end. One of such PA characteristics resides in the so-called large-signal IMD sweet-spots, i.e., a deep in the IMD vs. P in plot [16,17]. IMD sweetspots can be understood as the result of interactions between the PA mild and strong nonlinearities [18].…”
Section: Introductionmentioning
confidence: 99%